Análise do discurso crítica do conceito de Federalismo em período de crise: da independência à resistência democrática - Maia, Isabelly Cysne Augusto (2024)
As the discourse is permeated by situations of power and disputes over the meaning that will prevail, understand how federalism, the main mechanism for distributing power, was interpreted by the highest Court in the country, in one of the most severe periods of crisis, It is also about understanding how power struggles existing in the exogenous context crystallized in the Court's official speeches. Thus, the general objective of the research is to investigate whether the Federal Supreme Court (STF) would have acted in an institutionally independent way, considering the interpretations given to the concept of federalism in the years 2020 and 2021. Given this context, the Court would have been able to remain autonomous and independent, observing an essential pillar in the institutionalization process, or did it end up giving in to external pressure, losing in terms of institutionalization, with the promotion of changes in the process of redistribution of powers through federalism? To carry out this analysis, a corpus was created, consisting of twenty-eight decisions, arising from processes involving federative conflicts and consolidate in the context of concentrated control of constitutionality. The aforementioned decisions were analyzed using the critical discourse analysis (CDA) method, following the constructions of MAXQDA 2022. To answer the central research question and enable the achievement of the general objective, four specific objectives were established . Initially, the objective was to investigate the doctrinal concepts of federalism, crisis and institutionalism, clarifying the essential elements for conducting the research. Next, the exogenous context was presented, showing how the relationship between political powers occurred, during one of the most critical periods of the pandemic crisis, and then moving on to critical discourse analysis, indicating how the concept of Federalism was worked by the STF, in concentrated control decisions, during the years 2020 and 2021. Finally, the objective was to concatenate the concept of federalism, worked on by the Supreme Court in the period observed, with the concept of independence, doctrinally developed, highlighting the impact of the exogenous context on the Court’s position. It was concluded that, during the years 2020 and 2021, the STF constructed a new concept of federalism, with the establishment of new assumptions, which distance themselves from the constitutional text, demonstrating a normative, defensive and democracy-strengthening action, but which cannot be classified as independent, as the concept of federalism was instrumentalized to achieve other objectives, such as: speed in implementing public policies, strengthening subnational entities and hindering the advancement of authoritarian practices.